(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study investigates the formulation and characterization of mucoadhesive microspheres for Lansoprazole using chitosan as the primary polymer. The objectives were to enhance the drug's solubility and prolong its gastric retention. Various formulations were prepared via the solvent evaporation method, and their properties, including percentage yield, entrapment efficiency, stability in acidic conditions, flow characteristics, and drug release profiles, were evaluated. The results demonstrated that formulation F3 exhibited the highest percentage yield (75.45%) and entrapment efficiency (74.45%). Stability studies showed a gradual decline in transmittance in 0.1 N HCl, indicating some degradation of microspheres over time. The cumulative drug release in simulated gastric fluid revealed significantly lower release from chitosan microspheres compared to plain Lansoprazole, indicating a sustained release effect. Kinetic analysis suggested a zero-order release profile for formulation F3, highlighting its potential for controlled drug delivery. Overall, chitosan-based mucoadhesive microspheres present a promising approach to improving the therapeutic efficacy of Lansoprazole.